Exploiting Polarization Mismatch to Estimate the Orientation of Rotating UHF RFID Tags - Di Giampaolo, Emidio; Martinelli, Francesco; Romanelli, Fabrizio (IEEE journal of radio frequency identification (Online), 2023)
In this paper we propose a contactless system based on the RFID technology to estimate the rotation of a rotating tagged object. The rotating object is equipped with a linearly polarized RFID tag while the reader is endowed with a circularly polarized antenna. The estimation algorithm exploits the dependence of the phase of the backscattered RFID signal on the relative orientation between the tag's and the reader's antennas. It is based on an Extended Kalman Filter which only uses the phase measurements and assumes an approximate knowledge of the maximum expected torque (i.e., of the maximum rotation acceleration) applied to the object. Numerical and experimental results show that the orientation can be estimated with an error in the order of a few degrees. The maximum allowed rotation speed in online implementations mainly depends on the acquisition rate of the RFID reader, since the EKF-based algorithm can process more than 10 5 phase measurements per s.